Irrigation agriculture affects organic matter decomposition in semi-arid terrestrial and aquatic ecosystems - Arroita, Maite; Causape, Jesus; Comin, Francisco A.; Diez, Joserra; Jose Jimenez, Juan; Lacarta, Juan; Lorente, Carmen; Merchan, Daniel; Muniz, Selene; Navarro, Enrique; Val, Jonatan; Elosegi, Arturo (JOURNAL OF HAZARDOUS MATERIALS, 2013)
Many dryland areas are being converted into intensively managed irrigation crops, what can disrupt the hydrological regime, degrade soil and water quality, enhance siltation, erosion and bank instability, and affect biological communities. Still, the impacts of irrigation schemes on the functioning of terrestrial and aquatic ecosystems are poorly understood. Here we assess the effects of irrigation agriculture on breakdown of coarse organic matter in soil and water. We measured breakdown rates of alder and holm oak leaves, and of poplar sticks in terrestrial and aquatic sites following a gradient of increasing irrigation agriculture in a semi-arid Mediterranean basin transformed into irrigation agriculture in 50% of its surface. Spatial patterns of stick breakdown paralleled those of leaf breakdown. In soil, stick breakdown rates were extremely low in non-irrigated sites (0.0001-0.0003 day(-1)), and increased with the intensity of agriculture (0.0018-0.0044 day(-1)). In water, stick breakdown rates ranged from 0.0005 to 0.001 day(-1), and increased with the area of the basin subject to irrigation agriculture. Results showed that irrigation agriculture affects functioning of both terrestrial and aquatic ecosystems, accelerating decomposition of organic matter, especially in soil. These changes can have important consequences for global carbon budgets. (C) 2013 Elsevier B.V. All rights reserved.
The following values have no corresponding Zotero field: pub-location: PO BOX 211, 1000 AE AMSTERDAM, NETHERLANDS publisher: ELSEVIER SCIENCE BV
Keywords: breakdown; ecosystem functioning; Irrigation agriculture; Soil; Stream

Oak trees and soil interactions in Mediterranean forests: a positive feedback model - Aponte, Cristina; García, Luis V.; Pérez-Ramos, Ignacio M.; Gutiérrez, Eduardo; Marañón, Teodoro (Journal of Vegetation Science, 2011)
Questions: What is the spectrum of variability of chemical elements in a Mediterranean forest ecosystem across the different compartments? Do coexisting tree species with different leaf chemical composition and nutrient cycling distinctly modify soil conditions? Could these species-speciﬁc, treegenerated soil changes create a potential positive feedback by affecting longterm species distribution? Location: Mixed oak forests of southern Spain, Los Alcornocales Natural Park. Methods: We sampled and chemically analysed ﬁve different ecosystem components: leaves, leaf fall, litter and superﬁcial (0–25 cm) and sub-superﬁcial (25–50 cm) soil beneath the canopies of evergreen Quercus suber and deciduous Q. canariensis trees. We used multiple co-inertia analysis (MCoA) to conjointly analyse the patterns of variability and covariation of eight macro- and micronutrients determined in each of the sampled ecological materials. We implemented a path analysis to investigate alternative causal models of relationships among the chemical properties of the different ecosystem components. Results: Variability in the concentration of chemical elements was related to the nature of their biogeochemical cycles. However, the rank of element concentration was consistent across ecosystem components. Analysis of coinertia (MCoA) revealed that there was a common underlying multivariate pattern of nutrient enrichment in the ecosystem, which supported the hypothesis of a separation in biogeochemical niches between the two co-existing oak species, with Q. canariensis having richer plant tissues and more fertile soil directly under each tree than Q. suber. The feasibility of a potential tree–soil positive feedback model was the only statistically validated among several alternative (non-feedback) models tested. Conclusions: In the studied Mediterranean forests, oak species distinctly modify soil fertility conditions through different nutrient return pathways. Further investigation is needed to address whether these tree-generated soil changes could affect seedling establishment and ultimately inﬂuence species distribution.
Keywords: Biogeochemical niche; ecological stoichiometry; ecosystem functioning; Foliar analysis; nutrient cycling; Quercus canariensis; Quercus suber; Soil fertility

Improved understanding of drought controls on seasonal variation in Mediterranean forest canopy CO2 and water fluxes through combined in situ measurements and ecosystem modelling - Keenan, T.; Garcia, R.; Friend, A. D.; Zaehle, S.; Gracia, C.; Sabate, S. (BIOGEOSCIENCES, 2009)
Water stress is a defining characteristic of Mediterranean ecosystems, and is likely to become more severe in the coming decades. Simulation models are key tools for making predictions, but our current understanding of how soil moisture controls ecosystem functioning is not sufficient to adequately constrain parameterisations. Canopy-scale flux data from four forest ecosystems with Mediterranean-type climates were used in order to analyse the physiological controls on carbon and water flues through the year. Significant non-stomatal limitations on photosynthesis were detected, along with lesser changes in the conductance-assimilation relationship. New model parameterisations were derived and implemented in two contrasting modelling approaches. The effectiveness of two models, one a dynamic global vegetation model ({''}ORCHIDEE{''}), and the other a forest growth model particularly developed for Mediterranean simulations ({''}GOTILWA+{''}), was assessed and modelled canopy responses to seasonal changes in soil moisture were analysed in comparison with in situ flux measurements. In contrast to commonly held assumptions, we find that changing the ratio of conductance to assimilation under natural, seasonally-developing, soil moisture stress is not sufficient to reproduce forest canopy CO2 and water fluxes. However, accurate predictions of both CO2 and water fluxes under all soil moisture levels encountered in the field are obtained if photosynthetic capacity is assumed to vary with soil moisture. This new parameterisation has important consequences for simulated responses of carbon and water fluxes to seasonal soil moisture stress, and should greatly improve our ability to anticipate future impacts of climate changes on the functioning of ecosystems in Mediterranean-type climates.
APSAPSThe following values have no corresponding Zotero field: pub-location: BAHNHOFSALLEE 1E, GOTTINGEN, 37081, GERMANY publisher: COPERNICUS GESELLSCHAFT MBH
Keywords: ecosystem functioning; forest ecosystems; Mediterranean; water stress

Improved understanding of drought controls on seasonal variation in Mediterranean forest canopy CO2 and water fluxes through combined in situ measurements and ecosystem modelling - Keenan, T; Garcia, R; Friend, A D; Zaehle, S; Gracia, C; Sabate, S (BIOGEOSCIENCES, 2009)
Water stress is a defining characteristic of Mediterranean ecosystems, and is likely to become more severe in the coming decades. Simulation models are key tools for making predictions, but our current understanding of how soil moisture controls ecosystem functioning is not sufficient to adequately constrain parameterisations. Canopy-scale flux data from four forest ecosystems with Mediterranean-type climates were used in order to analyse the physiological controls on carbon and water flues through the year. Significant non-stomatal limitations on photosynthesis were detected, along with lesser changes in the conductance-assimilation relationship. New model parameterisations were derived and implemented in two contrasting modelling approaches. The effectiveness of two models, one a dynamic global vegetation model ({''}ORCHIDEE{''}), and the other a forest growth model particularly developed for Mediterranean simulations ({''}GOTILWA+{''}), was assessed and modelled canopy responses to seasonal changes in soil moisture were analysed in comparison with in situ flux measurements. In contrast to commonly held assumptions, we find that changing the ratio of conductance to assimilation under natural, seasonally-developing, soil moisture stress is not sufficient to reproduce forest canopy CO2 and water fluxes. However, accurate predictions of both CO2 and water fluxes under all soil moisture levels encountered in the field are obtained if photosynthetic capacity is assumed to vary with soil moisture. This new parameterisation has important consequences for simulated responses of carbon and water fluxes to seasonal soil moisture stress, and should greatly improve our ability to anticipate future impacts of climate changes on the functioning of ecosystems in Mediterranean-type climates.
APS
Keywords: ecosystem functioning; forest ecosystems; Mediterranean; water stress

Baseline characterization of major Iberian vegetation types based on the NDVI dynamics - Alcaraz-Segura, Domingo; Cabello, Javier; Paruelo, José (Plant Ecology, 2008)
We present an approach to derive baseline conditions for the radiation intercepted by vegetation in the largest remaining patches of homogeneous vegetation of the Iberian Peninsula. These baseline conditions can serve as a reference to assess environmental changes. We also characterized the major vegetation types of the Peninsula in the functional space deﬁned by the NDVI dynamics and analyzed the climatic controls of NDVI dynamics. We analysed the attributes of the NDVI seasonal dynamics: annual mean (NDVI-I), relative range (RREL), NDVI maximum and minimum values (MAX and MIN), months of MAX and MIN (MMAX and MMIN), and their inter-annual variabilities (1982–1999). We selected as reference sites only homogeneous pixels occupied by natural vegetation. We described their relationship with climatic variables using regression models. NDVI-I and RREL captured most of the variability of the NDVI annual proﬁle. Eurosiberian vegetation types were more productive, with winter minima and summer maxima. Mediterranean vegetation had summer minima and maxima distributed from autumn to spring. Interannual differences (higher in the Mediterranean) were low for NDVI-I and MAX and high for RREL and MIN. Precipitation was the main driver of NDVI-I for the Mediterranean pixels while temperature constrained it in the Eurosiberian ones. Seasonality (RREL) was associated with winter temperatures in Eurosiberian areas and with summer drought in Mediterranean ones. The Iberian vegetation types mainly differed in terms of total production and seasonality. Such differences were related to mean and inter-annual variation in precipitation and temperature associated with the Eurosiberian and Mediterranean climate zones. The NDVI dynamics allowed us to identify a functional signature for each vegetation type which captures differences that go beyond their range of climatic factors. Our baseline descriptions, based on a common approach to characterize vegetation functioning, are proposed as reference situations to evaluate the impact of environmental changes on the remaining large patches of single major natural and seminatural vegetation types.
Keywords: AVHRR/NOAA; ecosystem functioning; iberian peninsula; Normalized Difference Vegetation Index (NDVI); Regional analysis; Remote sensing

Baseline characterization of major Iberian vegetation types based on the NDVI dynamics - Alcaraz-Segura, Domingo; Cabello, Javier; Paruelo, José (Plant Ecology, 2008)
We present an approach to derive baseline conditions for the radiation intercepted by vegetation in the largest remaining patches of homogeneous vegetation of the Iberian Peninsula. These baseline conditions can serve as a reference to assess environmental changes. We also characterized the major vegetation types of the Peninsula in the functional space deﬁned by the NDVI dynamics and analyzed the climatic controls of NDVI dynamics. We analysed the attributes of the NDVI seasonal dynamics: annual mean (NDVI-I), relative range (RREL), NDVI maximum and minimum values (MAX and MIN), months of MAX and MIN (MMAX and MMIN), and their inter-annual variabilities (1982–1999). We selected as reference sites only homogeneous pixels occupied by natural vegetation. We described their relationship with climatic variables using regression models. NDVI-I and RREL captured most of the variability of the NDVI annual proﬁle. Eurosiberian vegetation types were more productive, with winter minima and summer maxima. Mediterranean vegetation had summer minima and maxima distributed from autumn to spring. Interannual differences (higher in the Mediterranean) were low for NDVI-I and MAX and high for RREL and MIN. Precipitation was the main driver of NDVI-I for the Mediterranean pixels while temperature constrained it in the Eurosiberian ones. Seasonality (RREL) was associated with winter temperatures in Eurosiberian areas and with summer drought in Mediterranean ones. The Iberian vegetation types mainly differed in terms of total production and seasonality. Such differences were related to mean and inter-annual variation in precipitation and temperature associated with the Eurosiberian and Mediterranean climate zones. The NDVI dynamics allowed us to identify a functional signature for each vegetation type which captures differences that go beyond their range of climatic factors. Our baseline descriptions, based on a common approach to characterize vegetation functioning, are proposed as reference situations to evaluate the impact of environmental changes on the remaining large patches of single major natural and seminatural vegetation types.
Keywords: AVHRR/NOAA; ecosystem functioning; iberian peninsula; Normalized Difference Vegetation Index (NDVI); Regional analysis; Remote sensing